From research to reality: Australian evidence‐based practice in autism education. Issue 4 (24th August 2021) - Garrad, Traci‐Ann; Rayner, Christopher; Pedersen, Scott; Cuskelly, Monica
Abstract: Many teachers are sporadic in using evidence‐based practice (EBP) concerning students with autism spectrum disorder (ASD). Numerous reasons have been posited for this. However, no single study has worked to understand the relative importance of identified criteria in the EBP decision‐making processes of teachers. Through the development of a new survey tool, the Evidence‐Based Practice Innovation Survey (EBPIAS), an exploration of the decision‐making process of Australian teachers in their adoption and cessation of EBP was undertaken. Teachers rated the perception that an EBP would meet the needs of their students as the most important criteria in determining their use of EBP. Conversely, the judgement that an EBP did not meet the needs of their student was the most important criteria in their decision to cease use. In comparing the relevant importance of identified criteria, teachers rated the perception of training as the second‐lowest consideration in their decision to adopt and cease using EBP. Consequently, there may need to be greater promotion of, or information concerning, the training required by teachers for effective implementation supporting a more balanced and holistic approach in assessing criteria impacting the adoption of EBP by teachers in the first instance, potentially lowering cessation rates.